Experimental synthesis of size-controlled TiO2 nanofillers and their possible use as composites in restorative dentistry - Dipika V. Raorane; Ramesh S. Chaughule; Suhas R. Pednekar; Anushree Lokur (Saudi Dental Journal)
The aim of this work was to obtain an efficient protocol with a green, fast and facile way to synthesize TiO2 NPs and its application as fillers for enhancement of desired dental properties of light curing dental composites.A comparative study comprised the fabrication of light curing restorative composite materials with incorporating different fillers with varying wt%, varying resin material composition, to determine optimal dental restoration by focusing on the physical properties of dental materials. It was observed that the as-prepared green synthesized TiO2 nanohybrid particles contributed to the improvement in physical properties, thus promoting the green and rapid synthesis of nanohybrid fillers. In addition, mechanical values for experimental cured resin materials with bare and surface modified fillers were obtained. The experimental light curing nanocomposites with 5 wt% (wt%) nanohybrid surface modified filler particles with BisGMA (60 wt%), TEGDMA (20 wt%) and UDMA (20 wt%) resin composition provided increased physical strength and durability with higher compressive stress 195.56 MPa and flexural stress 83.30 MPa. Furthermore, the dental property, such as polymerization shrinkage (PS) obtained from volumetric method was decreased up to 3.4% by the addition of nano-hybrid fillers. In addition to this, the biocompatible and antimicrobial nature of TiO2 and its aesthetics properties such as tooth-like color makes TiO2 favorable to use as fillers.This study presents a green and facile method for the synthesis of TiO2 nanohybrid particles that can be successfully used as fillers in an experimental light curing resin matrix for enhancing its dental properties. This describes the potential of the green synthesized TiO2 nanohybrid particles to use as fillers in restorative dentistry. Keywords: Green synthesis, Microwave synthesizer, TiO2 fillers, Light curing resin materials, Mechanical strength, Characterization